2016
DOI: 10.1097/ico.0000000000000852
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pseudoexfoliation on Corneal Transparency

Abstract: This research demonstrates that the presence of pseudoexfoliation material can cause decrease in the transparency of clear cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…12,13 Corneal endotheliopathy could also lead to changes in CCT, as supposed by several authors in the literature. 14 In agreement with current knowledge, 15,16 the conflicting results about the changes of CCT in eyes affected by PEX could be interpreted either as the consequence of reduced corneal cell density and morphological changes due to hypesthesia or as the expression of corneal swelling due to endothelial dysfunction. In our study, however, we did not find any significant changes in CCT between the two study groups, so the relationship between presence of PEM and stromal/endothelium alterations is not yet currently clear.…”
Section: Discussionsupporting
confidence: 82%
“…12,13 Corneal endotheliopathy could also lead to changes in CCT, as supposed by several authors in the literature. 14 In agreement with current knowledge, 15,16 the conflicting results about the changes of CCT in eyes affected by PEX could be interpreted either as the consequence of reduced corneal cell density and morphological changes due to hypesthesia or as the expression of corneal swelling due to endothelial dysfunction. In our study, however, we did not find any significant changes in CCT between the two study groups, so the relationship between presence of PEM and stromal/endothelium alterations is not yet currently clear.…”
Section: Discussionsupporting
confidence: 82%
“…This indicated that the severity of keratoconus may be correlated with the elevation of the corneal densitometry values, especially in the anterior layer. Elevated corneal densitometry also has been reported in the pathogenesis of various ocular surface disorders, which may compromise the corneal transparency, including keratitis,17 endothelial abnormality,18 and pseudoexfoliation syndrome 19. Misalignment of the corneal collagen has been noted in keratoconus 4.…”
Section: Discussionmentioning
confidence: 97%
“…Increased optical density of the corneal epithelium in PEX has not yet been reported in the literature. However, Cankaya et al observed that the presence of pseudoexfoliation material decreased the transparency of the cornea as a whole [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optical density of the cornea in patients with PEX has received little research attention. Recently, Cankaya et al confirmed that the presence of pseudoexfoliation material can decrease the transparency of the cornea [ 11 ]. However, Sekeroglu et al reported contradictory results, as corneal clarity was similar in patients with bilateral PEX and healthy controls [ 12 ].…”
Section: Introductionmentioning
confidence: 99%